Comparison of medical costs among patients using adalimumab and infliximab: a retrospective study (compairs). (13th March 2011) - Sussman, D A; Kubiliun, N; Chao, J; Mulani, P M; Gillis, C A; Yang, M; Lu, M; Abreu, M T
Abstract : Introduction: Anti-tumour necrosis factor (anti-TNF) medications have never been compared in a direct fashion under real-world circumstances. The purpose of this study was to compare healthcare utilisation and costs using insurance data for patients with Crohn's disease (CD) who newly initiated anti-TNF therapy with adalimumab (ADA) or infliximab (IFX). Methods: Patients with ≥2 diagnoses of CD (ICD-9-CM: 555.XX) who initiated ADA or IFX therapy between January 2000 and March 2009 were identified from the Medstat MarketScan database. Patients had to be continuously enrolled at least 6 months before and after anti-TNF initiation. Patients with prior biologic therapy (ie, anti-TNF or natalizumab) or colitis (ICD-9-CM: 556.x) were excluded. ADA and IFX groups were matched 1:1 using a propensity score stratified by age, residence, inpatient visit utilisation and steroid use at baseline. The primary endpoint was 6-month direct cost of healthcare. The secondary endpoints compared healthcare utilisation between groups. Results: After propensity matching, demographic, clinical and healthcare utilisation characteristics were similar between the ADA (n=623) and IFX (n=623) groups at baseline. During the 6-month interval following anti-TNF initiation, healthcare costs were significantly lower for ADA compared with IFX therapy (table 1 ). Table 1 PWE-026 Mean HealthCare Costs (Per Person) During the 6 Months After Initiating Anti-TNF Therapy (US $) All-Cause, ADA (n=623) All-Cause, IFX (n=623) CD-Relateda, ADA (n=623) CD-Relateda, IFX (n=623) Anti-TNF drug costs – – 10 709 12 401 Other prescription drug costs 1334b 1639 546 857 Total medical service–related costs 6842b 10 316 5199b 9059 Total healthcare costs (costs excluding anti-TNF agents) 18 885b (8176b ) 24 355 (11 955) 16 454b (5745b ) 22 316 (9916) a Based on diagnosis of CD or related comorbidities (eg, malnutrition, anaemia, abdominal symptoms, etc). b p<0.0005 vs IFX. c Medical costs other than hospitalisation and outpatient visits are not shown. Both all-cause and CD-related hospitalisation decreased for both ADA and IFX groups (not shown). Emergency department (ED) use and hospitalisation in the 6-month follow-up period were similar between groups. Conclusion: In this real-world analysis of patients with CD who newly initiated with ADA or IFX, ADA-treated patients had significantly lower healthcare costs. Hospitalisation and ED utilisation were similar between groups.